Conformational selectivity in molecular recognition: the influence of artificial receptors on the cis-trans isomerization of acylprolines - Vicent, Cristina; Hirst, Simon C; Garcia-Tellado, Fernando; Hamilton, Andrew D (Journal of the American Chemical Society, 1991)
The cis-trans isomerization of acylprolyl groups is a kinetically significant step in protein folding and, as such, has been the subject of intense scrutiny. This interest has increased with the recent identification of a family of enzymes that catalyze this interconversion and the important role that two of their number, cyclophilin and FK506 binding protein, play in immunosupression. The peptidyl prolyl isomerases (PPIases) have been investigated by spectroscopic, synthetic, and kinetic methods, and a catalytic mechanism involving amide-bond distortion has been proposed. We report herein that different synthetic receptors can discriminate between the two rotamers and so influence the acylproline s-cis-s-trans equilibrium.